The Impact Of Reflexive Learning Strategy On Mathematics Achievement By First Intermediate Class Students And Their Attitudes Towards E-Learning (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Reflected learning strategy has been identified as one of the modern strategies that contribute to the academic success of students in mathematics. With the increasing requirements and the global trend to modernize teaching methods, which focus on students and not the teacher, teachers pay great attention to the use of modern teaching methods and to find their impact on important variables. Therefore, the research aims to find the effect of a reflexive learning strategy on mathematics achievement by first-grade intermediate students and their attitudes towards e-learning in Baghdad. The research community consisted of first intermediate students for the first course for the academic year (2019-2020 AD), and the two researchers adopted the experimental research method, while the research sample was (50) students who were selected by random sample and divided into two groups, one experimental and the other control. The two tools that were used were the achievement test and a measure of the trend towards e-learning. The results indicated that there are statistically significant differences in academic achievement in favor of the experimental group, and students who studied the course through the strategy of reflexive learning were more effective and positive than those who studied by the traditional method, and within the experimental group there is a strong positive trend towards the use of e-learning in teaching.